Struktur pembiayaan dan risiko kecairan: analisis perbankan Islam domestik dan asing di Malaysia (Financing structure and liquidity risk: Analysis of domestic and foreign Islamic banks in Malaysia) - Yaakub, Noraini Mat; Abdul-Rahman, Aisyah; Sulaiman, Ahmad Azam (Penerbit Universiti Kebangsaan Malaysia, 2017)
Liquidity risk stems from the failure of a bank to meet the demand from the bank's liability to customer at an affordable cost in times of need. It mayleadto bank insolvency and could affect the stability of the financial system. The failure of banks to effectively manage the financing structure may increase default risk and eventually liquidity risk.This study investigatesand comparesthefinancing structure-liquidity risk relationships between theMalaysian domestic and foreign Islamic banks. We adopt two measures of liquidity risk, namely: liquidity coverage ratio (LCR) and net stable funding ratio(NSFR). While LCR is a short-run measure of liquidity risk (30 days), NSFR is a longer term measure of liquidity risk (one year). For financing structure, we use four measures, namely, real estate financing, specialization index (SPEC), and the stability of short-term (LCC) and long-term financing structure (VART).By using static panel regression of 10 domestic and 7 foreign Islamic banks for the period of 1994-2014, the results show that financing structure of domestic Islamic bankshave significant positive relationship with LCR. Specifically, by increasing financing to property sector as well as stability of short-term financing structure (LCC), the domestic Islamic banks are exposed to short-term liquidityrisk (LCR).However, there is an inverse relationshipswith NFSRfor the case of foreign Islamic banks, inferring that by increasing financing to property sector leads to decreasing longer term foreign Islamic banks' liquidity risk (NSFR). These contradicting results could be due to the prudent strategy byforeign Islamic banks in providing financing to less risky clients. It is crucial for policy makers at macro and micro levels to consider the behavior of financing structure in improving liquidity risk management framework for Islamic banks. In addition, by looking at the trend of a bank's financing structure, investors and customerscan have a picture of a bank's liquidity risk, thus helping them to make investment and savingdecisions.